Eco-Pesantren Program Shaping Islamic Character and Environmental Awareness: Program Eco-Pesantren dalam Pembentukan Karakter Islami dan Kesadaran Lingkungan - Makrufah, Nurul Ilmiyah Al; Abror, Sirojuddin (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Environmental degradation has increasingly positioned education and religious institutions as strategic arenas for cultivating ecological responsibility. Specific Background: Islamic boarding schools hold distinctive potential to integrate Islamic teachings with daily environmental practices, particularly within child-friendly pesantren contexts. Knowledge Gap: Existing studies tend to address environmental education in pesantren partially, without simultaneously integrating eco-pesantren programs, Islamic character formation, and child-friendly educational principles. Aims: This study aims to analyze the implementation of the Eco-Pesantren program in forming Islamic character and environmental awareness among students at the child-friendly At-Tahdzib Islamic Boarding School in Jombang. Results: Using a qualitative case study approach through participatory observation, in-depth interviews, and documentation, the findings show that integrating Islamic values with environmental conservation activities—such as Green Friday programs, automatic water faucets, tree planting, 3R-based waste management, and energy conservation—contributes to observable changes in students’ ecological behavior and character, including reduced ablution water use, decreased electricity consumption, increased waste sorting consistency, reduced plastic waste, and improved understanding of environmental jurisprudence. Novelty: The novelty of this study lies in its holistic integration of eco-pesantren practices, Islamic character education, and child-friendly pesantren principles within a contextual Islamic education model. Implications: These findings provide empirical and conceptual contributions for developing sustainable Islamic education models that align spiritual values with environmental responsibility. Highlights • Integration of Islamic values with daily environmental practices within pesantren life• Observable behavioral changes in water use, energy conservation, and waste management• Holistic Islamic education model aligned with child-friendly pesantren principles Keywords Eco-Pesantren; Islamic Education; Islamic Character; Environmental Awareness; Child-Friendly Pesantren